2020
DOI: 10.2169/internalmedicine.3943-19
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Earlobe Creases and Cardiovascular Events in Japanese Hemodialysis Patients: A Prospective Cohort Study

Abstract: Objective The earlobe crease, a wrinkle extending from the tragus to the outer border of the earlobe, is a well-known surrogate marker for a high risk of cardiovascular disease. However, information is lacking about its association with cardiovascular events among hemodialysis patients, who already have an increased risk of cardiovascular disease. We tested the hypothesis that earlobe creases are independently associated with the risk of cardiovascular events among Japanese hemodialysis patients. Methods This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Two studies also reported that the AUC value of traditional risk factors for CHD was increased by adding the presence of ELC. 5,6 Most studies used high-risk CHD patients as research subjects, but Wakasugi et al 20 used patients who were undergoing hemodialysis and reported conflicting results. Based on a four-year prospective cohort study, patients undergoing hemodialysis with ELC had increased cardiovascular disease incidence compared to patients without ELC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies also reported that the AUC value of traditional risk factors for CHD was increased by adding the presence of ELC. 5,6 Most studies used high-risk CHD patients as research subjects, but Wakasugi et al 20 used patients who were undergoing hemodialysis and reported conflicting results. Based on a four-year prospective cohort study, patients undergoing hemodialysis with ELC had increased cardiovascular disease incidence compared to patients without ELC.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial differences in traditional risk factors between hemodialysis patients and the non-dialysis population might influence the results. Wakasugi et al 20 reported that ELC was only a sign of ageing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations